2013
DOI: 10.1371/journal.pone.0063063
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Immunobiochemical Characterization of a 31 kDa Cross-Reactive Allergen from Phaseolus vulgaris (Kidney Bean)

Abstract: BackgroundLegumes are a rich source of proteins but are also potential elicitors of IgE-mediated food allergy. This study aimed to isolate and characterize a major allergen of Phaseolus vulgaris (kidney bean) and determine its allergenicity.MethodologyKidney bean allergen was purified using Q Sepharose column (anion exchanger) and eluates with high intensity were pooled to purify protein using Superdex 75 (gel filtration) and C18 column (RP-HPLC). Patients with history of kidney bean allergy were skin prick te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…[28] Kasera et al demonstrated that a purified allergen of 31 kDa from green bean was stable to boiling for 60 min. [25] Similar heat stability to boiling has also been shown for pea allergens in several studies. [24,37]…”
Section: Effects Of Boilingsupporting
confidence: 63%
See 1 more Smart Citation
“…[28] Kasera et al demonstrated that a purified allergen of 31 kDa from green bean was stable to boiling for 60 min. [25] Similar heat stability to boiling has also been shown for pea allergens in several studies. [24,37]…”
Section: Effects Of Boilingsupporting
confidence: 63%
“…In pea, Pis s ( Pisum sativum ) 3 was isolated and characterized as an ns‐LTP . In the case of green bean, several IgE‐binding proteins have been detected and partially characterized, but only an ns‐LTP from this legume has been described as a major allergen in a Spanish green bean‐allergic study population. The allergen has been completely characterized and named as Pha v ( Phaseolus vulgaris ) 3 .…”
Section: Allergen Characterization: Recent Advancesmentioning
confidence: 99%
“…Histamine release upon rRhi o 1 challenge was performed and percentage of histamine release was calculated as described previously [ 22 ]. Briefly, PBMC’s (2 x 10 5 ) were isolated from healthy donors by HiSep TM LSM 1077 (HiMedia Laboratories, India) and bound IgE’s were stripped off by incubating in lactic acid buffer (pH 3.5) for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Another similar membrane was blotted with pooled sera from 2 non-atopic patients for control experiment. 21 …”
Section: D 2d Western Blotting and Image Analysismentioning
confidence: 99%
“…External calibration 21 was done using peptide calibration standard II mixture (Bruker Daltonics). Acquisition of spectra was done using Autoflex II MALDI-TOF/TOF machine in linear mode equipped with a pulsed nitrogen laser (λ=337 nm, 50 Hz) at 54% power in the positive ion mode.…”
Section: In-gel Digestion and Maldi-tof Ms/ms Analysismentioning
confidence: 99%